PENGARUH GIRO WAJIB MINIMUM (GWM), SUKU BUNGA DEPOSITO BERJANGKA, DANA PIHAK KETIGA (DPK) DAN COST OF LOANABLE FUNDS TERHADAP BASE LENDING RATE (BLR) (Studi Pada Bank Swasta Nasional dan Bank Persero yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Hashifah Nabilah; Wisnu Mawardi (Faculty of Economics and Business Diponegoro University, 2016)
Base lending rate is the implementation process of the management of bank funding. Inbanking industry which more competitive, banks are required to offer a low base lendingrate. On the other hand, the banks had no motivation to maximize revenue. This study isaimed to analyze the effect of reserve requirements, deposit interest rates, third partyfunds and cost of loanable funds to the base lending rate.The samples used in this study are 14 private national banks and state-owned banks listedon the Indonesia Stock Exchange in 2010-2014. The method of this research is usingmultiple regression model with IBM SPSS Statistics 22 program to analyze the effect ofindependent variables to the dependent variable.The result shows that the deposit interest rate and the cost of the loanable funds havepositive and significant effect to the base lending rate. However, reserve requirementsand third party funds does not affect to base lending rate. These results proved that highinterest rates on time deposits are the bank's strategy to increase market share of timedeposits which is bank's largest sources of funding and the component that has thebiggest influence on BLR is COLF amounted to 33.79% of the components that formBLR.